TiO2:ZnO/CuO thin film solar cells prepared via reactive direct-current (DC) magnetron sputtering. (December 2022) - Wisz, G.; Sawicka-Chudy, P.; Wal, A.; Potera, P.; Bester, M.; Płoch, D.; Sibiński, M.; Cholewa, M.; Ruszała, M.
Highlights: The TiO2 :ZnO layer was fabricated from a self-produced Ti-ZnO target and used as emitter for the first time. Thin films of TiO2 :ZnO and copper oxide have been deposited by reactive DC magnetron sputtering. The structural, photovoltaic, and optical properties of TiO2 :ZnO/CuO thin film solar cells were analyzed. Abstract: TiO2 : ZnO/CuO thin-film solar cells are manufactured using reactive direct-current magnetron sputtering. For the first time, the TiO2 : ZnO layers have been used as an emitter in TiO2 : ZnO/CuO solar cells by self-produced Ti-ZnO targets. The structural and morphological characterization of the TiO2 :ZnO/CuO solar cells was studied using physical methods of investigation: X-ray diffraction (XRD), scanning electron microscopy (SEM), and current-voltage (I-V) characteristics. From the XRD study, thin films were observed in CuO, ZnO, TiO2 and Ti3 O5 phases. Basic morphological characterizations like thickness, mechanism of growth, and average grain sizes were analyzed via scanning electron microscopy. The thicknesses of the TiO2 : ZnO and CuO layers were in the range of 170 to 354 nm and from 508 to 1634 nm, respectively. Furthermore, average grain sizes of CuO layers were in the range of 40–150 nm. The I-V study confirms the photovoltaic behavior of TiO2 : ZnO/CuO thin-film solar cells. The open-circuit voltage (Voc ) and short-circuit current density (Jsc ) values of the photovoltaic devices ranged from 1.5 to 49.0 mV and from 0.45 to 7.26 µA/cm 3, respectively. Additionally, the authors calculated and analyzed the values of Pmax, Isc, FF, Rs and Rsh . Finally, the optical properties of the thin film were studied. The total light transmission through the structure does not exceed 25% and the absorption coefficient below 600 nm is in the range 2 × 10 4 –2 × 10 5 cm −1 . The maximum reflectance value is observed in the UV-visible region and does not exceed 42%. The extinction coefficient varies between 0.1 and 0.9 depending on the wavelength and sample. The refractive index at 400 nm depends on the sample and is in the range of 1.7 to 4.5. The obtained values of the optical band gap for the investigated samples are 1.02 eV, 1.25 eV, 1.26 eV and 1.28 eV.